Four new species of Ocellularia (lichenized Ascomycota: Graphidaceae) from Cuba, with a revised taxonomy of the O. bahiana complex and a key to thelotremoid taxa with small, brown, (sub-)muriform ascospores. (9th September 2015) - Unknown
Abstract: Four new species from Cuba are described in the genus Ocellularia, emphasizing the importance of the Caribbean for the diversification of lichen fungi and the level of unrecognized species richness in Ocellularia . Three of the new species belong in the O. bahiana group: O. coronata Lücking & Pérez-Ortega, differing from O. bahiana by the ridged to folded thallus, vertically ridged apothecia, and complex columella largely covering the disc; O. fuscospora Lücking & Pérez-Ortega, differing from O. urceolaris in the immersed to erumpent, columellate apothecia; and O. radiata Lücking, differing from O. bahiana in the complex, radiating columella filling the disc. In contrast, Ocellularia nigririmis Lücking & Pérez-Ortega is a species of the O. papillata morphodeme with immersed apothecia with a small, black-rimmed pore filled by a greyish black columella, and small ascospores. We also clarify the taxonomy and nomenclature of columellate taxa in the O. bahiana group and provide a key to all thelotremoid Graphidaceae with small, brown, (sub-)muriform ascospores. The new combination Ocellularia lunensis (Nagarkar & Hale) Lücking is proposed.